Dopant‐Free Hole‐Transporting Layer Based on Isomer‐Pure Tetra‐Butyl‐Substituted Zinc(II) Phthalocyanine for Planar Perovskite Solar Cells. Issue 9 (29th May 2019) - Dong, Lei; Hu, Qikun; Rezaee, Ehsan; Chen, Qian; Yang, Songhe; Cai, Siyuan; Liu, Bingchen; Pan, Jia-Hong; Xu, Zong-Xiang
Abstract : Herein, the important role of the isomer purity of hole‐transporting materials (HTMs) in achieving high‐performance perovskite solar cells (PSCs) is highlighted. The isomer‐pure 2, 9, 16, 24‐tetra‐ n ‐butyl‐Zn(II) phthalocyanine ( RE ‐ZnBu4 Pc) is directly synthesized through a ring expansion method, without any further purification. The ground‐state absorption, fluorescence and thermal properties of RE ‐ZnBu4 Pc and the isomer mixture ZnBu4 Pc, along with their hole mobilities and film morphologies are investigated, proving that RE ‐ZnBu4 Pc can be the more efficient HTM. The devices based on RE ‐ZnBu4 Pc, as dopant‐free HTMs, achieve a higher average power conversion efficiency (PCE of 11.49% ± 0.67%) and more stability at 25 °C and under 75% relative humidity than that of isomer mixture ZnBu4 Pc (PCE of 9.51% ± 1.15%). RE ‐ZnBu4 Pc‐based PSCs also show better reproducibility in the fabrication process. This study demonstrates that better device performance can be expected for PSCs with isomer‐pure HTM materials. Abstract : For the first time, isomer‐pure 2, 9, 16, 24‐tetra‐ n ‐butyl‐Zn(II) phthalocyanine ( RE ‐ZnBu4 Pc) is synthesized through ring expansion of symmetric tri‐ n ‐butyl‐substituted boron subphthalocyanine and is used as hole transporting material (HTM) in planar conventional perovskite solar cells (PSCs), offering higher efficiencies and better long‐term stabilities for these devices. Using isomer‐pure compounds as HTMs in PSCs can also improve the reproducibility of the device fabrication process.